2013
DOI: 10.1177/0734242x13507309
|View full text |Cite
|
Sign up to set email alerts
|

Waste management and contaminated site remediation practices after oil spill: A case study

Abstract: A case study is presented on waste management practices implemented after a residual fuel oil spill from a steam-generating boiler in an industrial area, and on the technical feasibility of monitored natural attenuation as a treatment option for a recently contaminated tropical soil. One day after contamination, surface soil total petroleum hydrocarbons and phenanthrene concentrations varied from 3.1 to 7.9 g kg(-1) and 149 to 287 µg kg(-1), respectively. Petroleum hydrocarbon concentrations decayed along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Experimental and case studies have shown that autochthonous bacterial communities are capable of adapting to oil contamination and degradation of oil-derived compounds (Acosta-González et al 2015; Oliveira et al 2013; Chikere et al 2012; Bento et al 2005). LH-PCR has been proved to be a sensitive method to monitor the successional changes in bacterial community (Yan et al 2016; Mikkonen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and case studies have shown that autochthonous bacterial communities are capable of adapting to oil contamination and degradation of oil-derived compounds (Acosta-González et al 2015; Oliveira et al 2013; Chikere et al 2012; Bento et al 2005). LH-PCR has been proved to be a sensitive method to monitor the successional changes in bacterial community (Yan et al 2016; Mikkonen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…9 The storage, transport, and proper disposal of the sorbent-generated physical waste significantly increases the oil cleanup costs. 15 Thus, oil recovery from the current oil spill remediation approaches is extremely tedious at best, requires significant resources, and fails to meet basic sustainability criteria for meaningful deployment. This is particularly alarming since oil spills have been occurring ever since the use of fossil fuels in society more than a century in the making.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They suggested several remediation options for the sludges including landfilling, incineration, co-processing in clinkerization furnaces, microwave liquefaction, centrifugation, destructive distillation, thermal plasma, low-temperature conversion, incorporation in ceramic materials, development of impermeable materials, encapsulation and biodegradation in land farming, bio-piles and bioreactors. Oliveira et al (2013) presented a case study of waste management practices implemented after a residual fuel oil spill from a steam-generating boiler in an industrial area. They found that natural attenuation can reduce the oil pollution.…”
Section: Introductionmentioning
confidence: 99%